2021
DOI: 10.1186/s12887-021-02856-0
|View full text |Cite
|
Sign up to set email alerts
|

The effect of intervelar veloplasty under magnification (Sommerlad’s Technique) without tympanostomy on middle ear effusion in cleft palate patients

Abstract: Objective Different surgical techniques and management approaches have been introduced to manage the cleft palate (CP) and its complications, such as otitis media with effusion (OME) and auditory problems. The optimal method, as well as the ideal time for palatoplasty and ventilation tube insertion, are the subject of controversy in the literature. We aimed to evaluate The Effect of Intervelar Veloplasty under Magnification (Sommerlad’s Technique) without Tympanostomy on Middle Ear Effusion in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Intergrouply, no difference was found either with ABR hearing threshold or 226-Hz tympanogram. The previous studies 9,11,12,14,[29][30][31][32] showed the special restoration of palatal muscles may or may not be beneficial to the hearing and the middle ear function. At least, it would not deteriorate the results.…”
Section: Resultsmentioning
confidence: 99%
“…Intergrouply, no difference was found either with ABR hearing threshold or 226-Hz tympanogram. The previous studies 9,11,12,14,[29][30][31][32] showed the special restoration of palatal muscles may or may not be beneficial to the hearing and the middle ear function. At least, it would not deteriorate the results.…”
Section: Resultsmentioning
confidence: 99%
“…One of the frequent complications, otitis media with effusion (OME), stands as the leading cause of conductive hearing loss in children with clefts. It tends to be both more prevalent and persistent compared with the general population 4–7 …”
Section: Introductionmentioning
confidence: 99%
“…It tends to be both more prevalent and persistent compared with the general population. [4][5][6][7] OME originates from the dysfunction of the eustachian tube, involving changes in para-tubal muscle architecture, tubal cartilage density, tubal curvature, and luminal diameter. These alterations facilitate inadequate ventilation and negative pressure within the middle ear cavity, culminating in OME and subsequent hearing loss.…”
mentioning
confidence: 99%
“…Following the closure of the palate layers, an intravelar veloplasty is performed to correct and change the position of the palatal muscles (5). Because of the improvements in palate performance, the patient's complaint about the complications decreases (6,7). If palate reconstruction is successful, the velopharyngeal area closes completely and the patient obtains the proper speech capability (6).…”
Section: Introductionmentioning
confidence: 99%